Effects of drafting on energy expenditure in in-line skating - Millet, G. P.; Geslan, R.; Ferrier, R.; Candau, R. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: The purpose of this study was to measure the effects of drafting on energy expenditure in in-line skating, and to investigate whether the ''benefit of drafting'', i.e. the decrease in energy expenditure, was different between two velocities and two distances separating the two skaters. Methods: Eight recreational in-line skaters performed six exercises of 6 min, at 2 velocities (V1 = 5.51±0.45 m·sec-1; V2 = 7.01±0.67 m·sec-1) in 3 conditions (ND = without drafting; D1=0.74-0.87 m ''close''; D2 = 1.19-1.36 m ''far''). Collection of expired gas was carried out using a breath-by-breath portable gas analyser K4b2 and the distance between the skaters was measured by video analysis. Results: The skaters' energy expenditure was reduced in all drafting conditions; between D1 and ND by 9.6±4.4% at V1 and by 2.7±3.3% at V2; between D2 and ND by 8.8±6.0% at V1 and by 4.2±4.8% at V2. This reduction was significantly (p<0.05) more important at V1 than V2 and no differences were observed between D1 and D2. Conclusion: In in-line skating, the technical difficulties for drafting efficiently, especially while cornering, resulted in a reduced ''benefit of drafting'' at high velocity than in other sports. Moreover, the need for the subject to adjust their own cycle frequency to that of the lead skater while drafting ''close'' would explain partly that there were no significant differences between drafting at D1 and D2. These results suggest that the drafting technique should be emphasized in training, especially in non-skilled skaters at high velocities and when cornering.